Manejo de residuos plásticos en las carreras de medio ambiente y agroindustria de la ESPAM MFL - Andrade Zambrano, María José (2017)
This research work had as a main objective to assess the linkages between the disposal of plastic waste and environmental quality aspects at the Environmental engineering and Agroindustry careers at ESPAM MFL University, the deductive and quantitative methods were used to deduce the benefits and to recommend strategies that contribute in a positive way to achieve good living. The method quantitative was used to measure, analyze, and validate all those results gotten during the research. Additionally, the directors of these careers were interviewed which served to collect information in order to build the diagnostic investigation. Another method of measuring public opinion was surveys which helped acquiring information about the plastic waste generation. Were also used the check list, a tool that identifies and verifies aspects and environmental impacts that interact with environmental factors. Leopold matrix served to identify and assess the interactions between actions and environmental factors, were diagnosed with the current situation of waste plastics at the careers as well, then selected aspects of environmental quality were weighted, which concluded that the plastic waste management plan helped that these resources should be reused in other activities and likewise to not increase air pollution because these have an effect adverse to the environment.